Longitudinal Metabolite Changes after Traumatic Brain Injury: A Prospective Pediatric Magnetic Resonance Spectroscopic Imaging Study - Holshouser, Barbara (J Neurotrauma, 2019)
The aims of this study were to evaluate longitudinal metabolite changes in traumatic brain injury (TBI) subjects and determine whether early magnetic resonance spectroscopic imaging (MRSI) changes in discrete brain regions predict 1-year neuropsychological outcomes. Three-dimensional (3D) proton MRSI was performed in pediatric subjects with complicated mild (cMild), moderate, and severe injury, acutely (6–17 days) and 1-year post-injury along with neurological and cognitive testing. Longitudinal analysis found that in the cMild/Moderate group, all MRSI ratios from 12 regions returned to control levels at 1 year. In the severe group, only cortical gray matter regions fully recovered to control levels whereas N-acetylaspartate (NAA) ratios from the hemispheric white matter and subcortical regions remained statistically different from controls. A factor analysis reduced the data to two loading factors that significantly differentiated between TBI groups; one included acute regional NAA variables and another consisted of clinically observed variables (e.g., days in coma). Using scores calculated from the two loading factors in a logistic regression model, we found that the percent accuracy for classification of TBI groups was greatest for the dichotomized attention measure (93%), followed by Full Scale Intelligence Quotient at 91%, and the combined memory Z-score measure (90%). Using the acute basal ganglia NAA/creatine (Cr) ratio alone achieved a higher percent accuracy of 94.7% for the attention measure whereas the acute thalamic NAA/Cr ratio alone achieved a higher percent accuracy of 91.9% for the memory measure. These results support the conclusions that reduced NAA is an early indicator of tissue injury and that measurements from subcortical brain regions are more predictive of long-term cognitive outcome.